A study to assess the problems and coping strategies among people living with HIV/AIDS at ART centre, Capital Hospital, Bhubaneswar, Odisha - Tudu, Priyanka (International Journal Of Community Medicine And Public Health, 2021)
Background: HIV/AIDS is one of the worst pandemics in today’s world that has a devastating physical and psychological effect. The virus has weakened the immune system of the body so much that they develop a number of different illnesses such as tuberculosis, pneumonia, persistent diarrhea and fever and skin infections. Methods: A quantitative research approach, descriptive survey research design was undertaken to assess the problems and coping strategies among HIV/AIDS patients. Purposive sampling technique was adopted to select the 100 HIV/AIDS patients. The study was conducted was at ART centre, Capital hospital Bhubaneswar. Data was collected through questionnaire by interviewing method. Results: The physical problems 76 (76%) had moderate problems and mean score (5.41±1.28), were psychological problems 60 (60%) had moderate problems and mean score (4.20±1.17) and financial problems 57 (57%) had moderate problems mean score (2.97±0.95). The coping strategies mean score (67.27±4.49). Chi square test was performed to find out the association between problems and coping strategies. Conclusions: The study was concluded with recommendation for descriptive study on large sample.